Halometallate-based ionic liquid catalysts - Leu, Meike K. (2020)
This work focuses on the synthesis and characterisation of halometallate ionic liquids (ILs), including Co(II), Ni(II), Cu(II), Zn(II), In(III), and Fe(III) metal halides. Due to their Lewis acidic nature, halometallate ILs are promising candidates as catalysts. In addition, ILs show advantageous properties (e.g. low vapour pressure and good ionic conductivity) for their use in catalytic applications using inductive heating methods such as microwave (MW) radiation or magneto-thermal heating. As for any catalyst the understanding of the catalytically active species and the properties of the respective catalyst are fundamental to explain the catalytic process. As to the best of our knowledge, no phase diagram has been reported for mixtures of [C1C4Im]Cl/CoCl2 and [C1C4Im]Cl/NiCl2, these were prepared to further understanding of discrete anion formation. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) were used to prepare the phase diagram and it is demonstrated how small changes in mole fraction lead to significant changes in thermal behaviour. In addition, Raman spectroscopy and X-ray photoelectron spectroscopy (XPS) were used to find additional evidence for anions formed. However only the formation of [MCl4]- could be observed.